Know your Bible : a self-guided tour through God's word - Kent, Paul. (Uhrichsville, Ohio : Barbour Books, an imprint of Barbour Publishing, Inc., 2015)
"You want - and need - to know your Bible ... and here's a powerful tool to help you: a fully illustrated, self-guided tour of God's Word. Know Your Bible is a brand-new, multi-level study of scripture, based on the two-million-selling handbook by the same name. This enhanced, fully illustrated edition includes one-, three-, six-, and twelve-month courses for you to choose the depth of study you want to pursue. From a very basic overview of scripture to an intensive study of the great themes, characters, and stories of each Bible book, this exciting reference provides the framework you need to truly understand God's Word - to know your Bible" -- Barnes & Noble.
Keywords: Bible -- Handbooks, manuals, etc; Bible -- Study and teaching